A randomized Phase III clinical trial to assess the efficacy of a bovine-human reassortant pentavalent rotavirus vaccine in Indian infants. Issue 45 (27th October 2017) - ; Shaikh, Hanif; Gupta, Lalit; Patil, Rakesh; Aslam, Mohd.; Arya, Alok; Rafiqi, Farhana; Gupta, Subodh S.; Maliye, Chetna H.; Bahulekar, P.V.; Bala, Kiran; Nazir Shora, Tajali; et al.
Highlights: Pentavalent reassortant rotavirus vaccine was tested for efficacy in infants. The vaccine (BRV-PV) showed excellent tolerability and a good safety profile. Primary analysis efficacy was 36% against SRVGE and up to 60.5% against VSRVGE. The efficacy through 2 years of age was 39.5% (SRVGE) and 54.7% (VSRVGE). The intent to treat analyses confirmed all the per protocol analyses. Abstract: Rotavirus is the most common cause of moderate-to-severe infant diarrhoea in developing countries, resulting in enormous morbidity, mortality, and economic burden. A bovine-human reassortant pentavalent rotavirus vaccine (BRV-PV) targeting the globally most common strains was developed in India and tested in a randomized, double-blind, placebo-controlled end-point driven Phase III efficacy clinical trial implemented at six sites across India. Infants 6 to 8 weeks of age were randomized (1:1) to receive three oral doses of BRV-PV or placebo at 6, 10, and 14 weeks of age along with routine vaccines. Home visit surveillance was conducted to detect severe rotavirus gastroenteritis (SRVGE) and safety outcomes until the children reached two years of age. A total of 3749 infants received BRV-PV while 3751 received placebo. At the time of the primary end-point (when the minimum number of cases needed for analysis were accrued) the vaccine efficacy against SRVGE was 36% (95% CI 11.7, 53.6, p = 0.0067) in the per protocol (PP) analysis, and 41.9% (95% CI 21.1, 57.3, p = 0.0005) in the intent to treat (ITT) analysis. Vaccine efficacy over the entire follow-up period (until children reached two years of age) was 39.5% (95% CI 26.7, 50, p < 0.0001) in the PP analysis and 38.8% (95% CI, 26.4, 49, p < 0.0001) in the ITT analysis. Vaccine efficacy against the very severe rotavirus cases (VSRVGE, Vesikari score ≥ 16) was 60.5% (95% CI 17.7, 81, p = 0.0131) at the time of the primary analysis and 54.7% (95% CI 29.7, 70.8, p = 0.0004) for the complete follow-period in the PP population. The incidence of solicited, unsolicited, and serious adverse events were similar in both the vaccine and placebo groups. Likewise, the number of intussusceptions and deaths were similar between both groups. Thus, BRV-PV is an effective, well tolerated and safe vaccine in Indian infants. (Trial registration: Clinical Trials.Gov [NCT 02133690 ] and Clinical Trial Registry of India [CTRI/2013/05/003667 ]).